Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Ta có (3 - 2i)z + (4 + 5i) = 7 + 3i <=> (3 - 2i)z = 7 + 3i - 4 - 5i
<=> z = <=> z = 1. Vậy z = 1.
b) Ta có (1 + 3i)z - (2 + 5i) = (2 + i)z <=> (1 + 3i)z -(2 + i)z = (2 + 5i)
<=> (1 + 3i - 2 - i)z = 2 + 5i <=> (-1 + 2i)z = 2 + 5i
z =
Vậy z =
c) Ta có + (2 - 3i) = 5 - 2i <=> = 5 - 2i - 2 + 3i
<=> z = (3 + i)(4 - 3i) <=> z = 12 + 3 + (-9 + 4)i <=> z = 15 -5i
\(\Leftrightarrow\left(i^2+4i+4\right)\left(1-i\right)z=4-3i+\left(3+i\right)z\)
\(\Leftrightarrow\left(4i+3\right)\left(1-i\right)z-\left(3+i\right)z=4-3i\) (do \(i^2=-1\Rightarrow i^2+4=3\))
\(\Leftrightarrow\left(4i-4i^2+3-3i\right)z-\left(3+i\right)z=4-3i\)
\(\Leftrightarrow\left(7+i\right)z-\left(3+i\right)z=4-3i\)
\(\Leftrightarrow4z=4-3i\)
\(\Leftrightarrow z=1-\dfrac{3}{4}i\)
Z= a+bi và \(\overline{Z}\) =a-bi → (1+2i).(a+bi) +(1+2a-2bi)i =1+3i
→a+bi +2ai -2b +i +2ai +2b=1+3i (i2= -1)
→ a+ (4a+b+1)i = 1+3i
→\(\begin{cases}a=1\\4a+b+1=3\end{cases}\) → a=1 , b=-2 → modum : \(\left|Z\right|\)=\(\sqrt{5}\)
gọi z= a + bi \(\left(a,b\in R\right)\)
(2+i)(a+bi)=4-3i
\(\Leftrightarrow\) \(2a-b+\left(a+2b\right)i=4-3i\)
\(\Leftrightarrow\begin{cases}2a-b=4\\a+2b=-3\end{cases}\)
\(\Leftrightarrow\begin{cases}a=1\\b=-2\end{cases}\)
\(z=1-2i\)
w= i(1-2i) + 2( 1+ 2i) = 4 + 5i
Gọi \(z=a+bi\left(a,b\in R\right)\)
\(\left(2+i\right)\left(a+bi=4-3i\right)\)
\(\Leftrightarrow2a-b+\left(a+2b\right)i=4-3i\)
\(\Leftrightarrow\begin{cases}2a-b=4\\a+2b=-3\end{cases}\)
\(\Leftrightarrow\begin{cases}a=1\\b=-2\end{cases}\)
\(z=1-2i\)
\(w=i\left(1-2i\right)+2\left(1+2i\right)=4+5i\)
câu này hay thế!